Avaliação da acuidade visual para perto das pessoas que preparam doses de insulina - Carvalho, Gerdane Celene Nunes (2015)
There are studies that show the insulin preparation technique errors with out, however, identifying the profile of visual acuity close to those who prepare and therefore without establishing a relationship of decreased visual acuity close to glycemic control, in which decompensation may be consequences arising out of errors in t he preparation of doses. It aimed to evaluate visual acuity for near people who prepare insulin doses at home. It is an exploratory, observational and cross - sectional study conducted from September / 2013 to April / 2015 twenty Health Strategies Family the urban area of Picos - PI. Composed the sample 100 type 1 diabetics and insulin 2, being the person responsible for insulin preparation itself diabetic or someone else. To collect, held from December / 2014 to January / 2015, were scheduled visits and appl ied form with socioeconomic and clinical variables, assessment of visual acuity closer to the people who prepare insulin doses with Jaeger card, blood collection for dosage glycated hemoglobin and fingerstick to perform the blood glucose in diabetics. For data analysis we used the Statistical Package for Social Sciences (SPSS) version 19.0. For inferential analyzes mean comparison was used the Kruskal - Wallis test. The qualitative variables were assessed by Fisher's exact test. The project was submitted to t he Ethics Committee on Human Research of the Health of the State University of Piauí Science Center Beings and approved under the Protocol 901,145. The results showed that the average age of diabetics was 59 years, the prevalence of 52% males, 20% with inc omplete primary education, and 27% belonging to the C2 class. Of diabetics, 35% were dependent on third parties for the preparation of insulin doses, 80% of female officers, with an average of 45 years, and 31.4% had completed high school. The clinical var iables of diabetics, 34% were 11 - 20 years of diagnosis, 84% had type 2 diabetes, 73% and 86% had high blood glucose and glycated hemoglobin, respectively. In the evaluation of visual acuity for near 27% enxergaram the J1 level, 40% in J2, J3 16%, 7% in the J4, J5 2%, 3% J6, and 5% did not see any point on the card Jaeger, 33% had visual acuity decreased to near, with a prevalence of 40% in diabetics and 20% in other people responsible for preparing, presenting significant association with age and economic c lass. Given the loss of glycemic control in diabetics, the study shows the need to strengthen monitoring by the Family Health Strategy. For visual acuity, it is made mandatory to carry out ophthalmological screening in primary care of the people who prepar e insulin, as well as monitoring in reference to the expert. Thus, users, health professionals and managers should strengthen co - responsibility, assuming their role in the current health paradigm to minimize the problems identified.